Evaluation of macular neovascularization activity in pathological myopia: a comparison between optical coherence tomography and OCT-angiography - Li, Xin; Jing, Ruixia; Li, Xue; Wang, Zhen (Frontiers in Medicine, 2023)
Purpose The purpose of this study was to suggest a novel approach to assess the activity of macular neovascularization (MNV) activity in pathological myopia (PM) by comparing optical coherence tomography (OCT) with OCT-angiography (OCT-A).The Zeiss Cirrus HD-5000 was used to obtain OCT and OCT-A images of PM-MNV. The objective was to examine the characteristics of PM-MNV lesions and investigate the relationship between PM-MNV activity and changes in retinal structure in 54 patients (54 eyes). To analyze the OCT parameters associated with PM-MNV activity and their clinical significance in terms of sensitivity and specificity, using OCT-A as a reference.This study included 72 patients (72 eyes), of which 54 had good image quality and were considered for analysis. The study evaluated various OCT characteristics of MNV lesions, including the elevation external limiting membrane (ELM), ellipsoidal zone (EZ), retinal pigment epithelium (RPE) elevation, and EZ/RPE interruption, to identify possible parameters associated with PM-MNV activity. The inter-observer consistency found to be almost perfect. In the evaluation of PM-MNV activity, the sensitivity of ELM elevation, EZ interruption and RPE interruption were found to be 66.7% (low), 88.4% (high) and 95.6% (high), respectively, However, the specificity was found to be 71.4% (moderate), 71.4% (moderate) and 25.4% (poor), respectively. This indicates that the current evaluation methods were not accurately assessing PM-MNV activity. We developed a new comprehensive method that used EZ interruption as primary parameter and ELM elevation and RPE interruption as secondary parameters to evaluate PM-MNV activity with sensitivity of 97.8% and specificity of 85.4%.In PM-MNV, a novel comprehensive diagnostic method combining EZ interruption, ELM elevation and RPE interruption might be a valuable indicator to evaluate PM-MNV activity.